(untitled) (Amsterdam, 1994)
The objective of this book is to provide information to be used as a basis for evaluating the fragile, shaky structure of global food production. The volume analyses the data by region and by intensity of cultivation; and furnishes information about the yield response, giving some indication of the health of the plants. It will be invaluable to all plant and crop scientists as well as to agriculturalists.
Keywords: Cây trồng, Bảo vệ cây trồng,Food crops,Cash crops,Plants, Protection of,Agricultural estimating and reporting,Food supply,Cây lương thực